An Analysis of Illocutionary Acts of The Main Characters Shown in The Nun Movie (2018) - I Wayan Yogi Astrawan; Ni Ketut Alit Ida Setianingsih; I Nyoman Arya Wibawa (CV. ULIL ALBAB CORP, 2024)
This paper explores the illocutionary acts performed by the main characters in the 2018 movie